2001
DOI: 10.1080/10473289.2001.10464273
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of PM10 and PM25 in Five Chilean Cities Using Factor Analysis

Abstract: Chile is a fast-growing country with important industrial activities near urban areas. In this study, the mass and elemental concentrations of PM 10 and PM 2.5 were measured in five major Chilean urban areas. Samples of particles with diameter less than 10 µm (PM 10 ) and 2.5 µm (PM 2.5 ) were collected in 1998 in Iquique (northern Chile), Valparaíso, Viña del Mar, Rancagua (central Chile), and Temuco (southern Chile). Both PM 10 and PM 2.5 annual mean concentrations (PM 10 : 56.9-77.6 µg/m 3 ; PM 2.5 : 22.4-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
77
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 31 publications
11
77
0
6
Order By: Relevance
“…Based on the loadings of PAHs and n-alkanes, four factors (sources) were identified: high-temperature combustion, fugitive emissions from oil residues, biogenic sources, and unburned fuels. The results of this study are in good agreement with the estimates made by Chen et al 237 Further study by Kavouras et al 238 reported source contributions of PAHs in several cities in Chile and compared the results with Santiago. Tsapakis et al 239 reported on-road and nonroad engine emissions as the main sources of carbonaceous aerosols in fine particle samples in Santiago.…”
Section: Beijing Chinasupporting
confidence: 82%
“…Based on the loadings of PAHs and n-alkanes, four factors (sources) were identified: high-temperature combustion, fugitive emissions from oil residues, biogenic sources, and unburned fuels. The results of this study are in good agreement with the estimates made by Chen et al 237 Further study by Kavouras et al 238 reported source contributions of PAHs in several cities in Chile and compared the results with Santiago. Tsapakis et al 239 reported on-road and nonroad engine emissions as the main sources of carbonaceous aerosols in fine particle samples in Santiago.…”
Section: Beijing Chinasupporting
confidence: 82%
“…The relationship between ambient PM level and actual personal exposures was examined. Correlation coefficients between the general ambient outdoors and personal exposure levels were 0.92 for both PM 2.5 and PM 10 .…”
Section: Introductionmentioning
confidence: 93%
“…The relationship between ambient PM level and actual personal exposures was examined. Correlation coefficients between the general ambient outdoors and personal exposure levels were 0.92 for both PM 2.5 and PM 10 .Bangkok air quality data for 1997-2000, including 24-hr average PM 10 , NO 2 , SO 2 , and O 3 from eight PCD monitoring stations, were analyzed and validated. The annual arithmetic mean PM 10 of the PCD data at the roadside monitoring stations for the last 3 years decreased from 130 to 73 µg/m 3 , whereas the corresponding levels at the general monitoring stations decreased from 90 to 49 µg/m 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rapid motorization in Beijing has resulted in serious congestion and the average network travel speed decreasing by 3.2% and 4.9%, respectively, within the 5th Ring Road during 2010 in AM and PM peak hour [4]. According to the United States Environmental Protection Agency, motor vehicles are an important source of air pollutants including carbon monoxide (CO), oxides of nitrogen (NO x ), sulfur dioxide (SO 2 ), volatile organic compounds (VOC), and particulate matter (PM) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%